Association of Clinicopathological Factors with Radiation Induced Oral Mucositis in Patients with Head and Neck Carcinoma - Uzma Zareef; Afifa Razi; Rehan Imad; Atif Iqbal (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2022)
Objective: